Basic psychological needs mediate connectedness and meaning in life among Chinese college students - Yaoyao Cai; Danling Zhan (Scientific Reports)
Abstract According to the China National Mental Health Development Report (2021–2022), only 46.7% of Chinese university students report experiencing meaning in life (MIL), while approximately 40% exhibit existential confusion, highlighting a critical psychological challenge. This study examines, in Chinese college students, how connectedness (to self, others, and nature) relates to meaning in life and whether basic psychological needs mediate these associations, integrating variable- and person-centered approaches. A cross-sectional study was conducted with 807 college students (mean age = 19.40 ± 1.25 years, 75.22% female) from colleges in Guangdong Province, China. Participants completed validated scales assessing connectedness to self (mindfulness), others (social connectedness), and nature, along with basic psychological needs and MIL. Both variable-centered (parallel mediation analysis) and person-centered (latent profile analysis) approaches were employed to provide complementary perspectives on the research questions. Variable-centered analysis confirmed mediation by basic psychological needs across all connectedness dimensions, with competence satisfaction showing the strongest effect (β = 0.20, 95% CI [0.13, 0.27]). Person-centered analysis identified three distinct connectedness profiles: Alienated Type (7.56%, characterized by low connectedness across dimensions), Moderated Type (65.43%, moderate connectedness levels), and Enriched Type (27.01%, high connectedness across all dimensions). Profile-based mediation analysis confirmed competence satisfaction as the primary mediator, with the Enriched Type showing the strongest indirect effect relative to the Alienated Type (β = 0.60, 95% CI [0.38, 0.84]). Our findings demonstrate that competence satisfaction is the primary mechanism linking multifaceted connectedness to MIL in Chinese college students. The distinct profiles underscore the need for tailored interventions rather than one-size-fits-all approaches. This study extends self-determination theory by revealing how integrated connectedness patterns foster MIL, offering a novel framework for targeted well-being initiatives for Chinese college students.